Wound Healing: Tensional Factor Pathomechanism In Occurance Of Abnormal Scar - Laksono, Gerardo AK; Tahalele, Paul L; Anggorwasito, Jose L; Wihastyoko, HYL (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Wound healing is a series of biophysiological processes, beginning with tissue injury, and ending with repairs from the wound tissue itself to a complete state consisting of several phases including inflammation, proliferation and remodeling. Every process of wound healing always leaves a scar. Hypertrophic and keloid is a product of abnormal wound healing. This abnormal scar formation is influenced by several factors, one of which is the wound stress. A tension that is too large in a wound will cause a hypoxic state in the wound itself. This hypoxic state will cause recurrent inflammation which leads to abnormal scar formation. One of abnormal scars formation prevention is reduction in wound tension. Reduction in wound tension reduce the inflammation process.